The Effect Of Perceived Price And Service Quality On Purchasing Decisions For Electronic Services (Survey On Customers Of Computer Kios & Services Singaparna) - Lulu Alfiani Mardian; Suci Putri Lestari; Dudu Risana (Penerbit Jurnal Indonesia, 2023)
This research used in this research is quantitative research. This study describes the influence of perceived price and service quality on service purchasing decisions at computer & service kiosks in Singapore. So the type of research taken is quantitative research with a Causal Descriptive survey method. The survey in this study was for customers of Singaparna Computer & Service Kiosks with a sample of 100 respondents. The data used are primary and secondary data. The data analysis technique used is Multiple Liner Regression Analysis using SPPS V.25 Software. The results of this study indicate that simultaneously perceived price and service quality have a significant effect on purchasing decisions. Partially Perceived Price has a significant influence on Purchasing Decisions. Partially, service quality has a significant influence on purchasing decisions.